Cell Death-Autophagy Loop and Glutamate-Glutamine Cycle in Amyotrophic Lateral Sclerosis - Yuan, Shu; Zhang, Zhong-Wei; Li, Zi-Lin (Frontiers in Molecular Neuroscience, 2017)
Although we know that amyotrophic lateral sclerosis (ALS) is correlated with the glutamate-mediated corticomotor neuronal hyperexcitability, detailed ALS pathology remains largely unexplained. While a number of drugs have been developed, no cure exists so far. Here, we propose a hypothesis of neuronal cell death–incomplete autophagy positive-feedback loop–and summarize the role of the neuron-astrocyte glutamate-glutamine cycle in ALS. The disruption of these two cycles might ideally retard ALS progression. Cerebrovascular injuries (such as multiple embolization sessions and strokes) induce neuronal cell death and the subsequent autophagy. ALS impairs autophagosome-lysosome fusion and leads to magnified cell death. Trehalose rescues this impaired fusion step, significantly delaying the onset of the disease, although it does not affect the duration of the disease. Therefore, trehalose might be a prophylactic drug for ALS. Given that a major part of neuronal glutamate is converted from glutamine through neuronal glutaminase, glutaminase inhibitors may decrease the neuronal glutamate accumulation, and, therefore, might be therapeutic ALS drugs. Of these, Ebselen is the most promising one with strong antioxidant properties.